Analysis of Several Physical Phenomena Measured on the Metallic Materials Cut by Abrasive Water Jets (AWJ) - Gřunděl, Jakub; Hlaváč, Libor M; Pětroš, Petr; Gembalová, Lucie (Materials (Basel, Switzerland), 2022)
Cutting using an abrasive water jet is a complex process involving several physical phenomena. This research studies some of them, mostly the influence of selected variables on the measured forces and vibrations. The traverse speed represents one of the key parameters when cutting using the AWJ. In the presented research, a set of experiments was performed on twelve different metal samples, while the force sensor measured the exerted forces and accelerometers measured the vibrations. Ten different types of steel samples of the same dimensions were cut applying five different traverse speeds. The data obtained during these measurements show that an increase in the traverse speed leads to an increase in the measured forces and vibrations. An analogous experiment performed on bronze and duralumin samples of the same dimensions, having applied higher speeds to compensate for the difference in the material structure and properties, completes the presented data. The most important results of the research are that exerted forces in the z-axis are higher than those in the x-axis, whereas measured vibrations are higher in the x-axis. According to our research, the elemental structure, especially the carbide formation, affects the measured forces and vibrations substantially.
Keywords: forces; cutting; normal force; traverse speed; tangential force; abrasive water jet; vibrations